Management of epithelial cancer of the ovary, fallopian tube, and primary peritoneum. Short text of the French Clinical Practice Guidelines issued by FRANCOGYN, CNGOF, SFOG, and GINECO-ARCAGY, and endorsed by INCa. (May 2019) - Lavoue, V.; Huchon, C.; Akladios, C.; Alfonsi, P.; Bakrin, N.; Ballester, M.; Bendifallah, S.; Bolze, P.A.; Bonnet, F.; Bourgin, C.; Chabbert-Buffet, N.; Collinet, P.; et al.
Abstract: An MRI is recommended for an ovarian mass that is indeterminate on ultrasound. The ROMA score (combining CA125 and HE4) can also be calculated (Grade A). In presumed early-stage ovarian or tubal cancers, the following procedures should be performed: an omentectomy (at a minimum, infracolic), an appendectomy, multiple peritoneal biopsies, peritoneal cytology (grade C), and pelvic and para-aortic lymphadenectomies (Grade B) for all histologic types, except the expansile mucinous subtypes, for which lymphadenectomies can be omitted (grade C). Minimally invasive surgery is recommended for early-stage ovarian cancer, when there is no risk of tumor rupture (grade B). Adjuvant chemotherapy by carboplatin and paclitaxel is recommended for all high-grade ovarian and tubal cancers (FIGO stages I-IIA) (grade A). For FIGO stage III or IV ovarian, tubal, and primary peritoneal cancers, a contrast-enhanced computed tomography (CT) scan of the thorax/abdomen/pelvis is recommended (Grade B), as well as laparoscopic exploration to take multiple biopsies (grade A) and a carcinomatosis score (Fagotti score at a minimum) (grade C) to assess the possibility of complete surgery (i.e., leaving no macroscopic tumor residue). Complete surgery by a midline laparotomy is recommended for advanced ovarian, tubal, or primary peritoneal cancers (grade B). For advanced cancers, para-aortic and pelvic lymphadenectomies are recommended when metastatic adenopathy is clinically or radiologically suspected (grade B). When adenopathy is not suspected and when complete peritoneal surgery is performed as the initial surgery for advanced cancer, the lymphadenectomies can be omitted because they do not modify either the medical treatment or overall survival (grade B). Primary surgery (before other treatment) is recommended whenever it appears possible to leave no tumor residue (grade B). After primary surgery is complete, 6 cycles of intravenous chemotherapy (grade A) are recommended, or a discussion with the patient about intraperitoneal chemotherapy, according to her risk-benefit ratio. After complete interval surgery for FIGO stage III disease, hyperthermic intraperitoneal chemotherapy (HIPEC) can be proposed, in accordance with the modalities of the OV-HIPEC trial (grade B). In cases of postoperative tumor residue or in FIGO stage IV tumors, chemotherapy associated with bevacizumab is recommended (grade A).